Flexible freestanding carbon nanofiber mats decorated with Zn/Co oxide nanostructures derived from zeolitic imidazolate frameworks as supercapacitor electrodes - Jungwoo Huh; Mayagozel Abdyrahymowa; Bhavana Joshi; Edmund Samuel; Ali Aldalbahi; Mostafizur Rahaman; Kim, Hee Jin; Lee, Min Wook; Sam S. Yoon (Elsevier BV, 2025)
Carbon nanofibers (CNFs) are excellent materials for hosting metal？carbon？nitrogen frameworks derived from zeolitic imidazole frameworks (ZIFs) that exhibit high electrical conductivity for energy storage devices. In this study, polyacrylonitrile (PAN) nanofibers are decorated with a Zn？Co bimetallic ZIF under open-air conditions using an eco-friendly water solvent and a wet chemical impregnation method to produce freestanding ZnO/CoOx@CNF supercapacitor electrodes. Highly textured Zn-based ZIFs or ZIF-L(Zn) PAN fibers are produced by optimizing the salt？ligand concentration ratio. Moreover, highly textured Co-based ZIFs and ZIF-L(Co) PAN fibers are fabricated. Finally, the optimal concentrations are used to synthesize PAN nanofibers decorated with Zn and Co bimetallic ZIFs. The Zn？Co-decorated PAN nanofibers are then carbonized at 800 °C in an Ar environment to construct a ZnO/CoOx@CNF supercapacitor. Using an aqueous electrolyte (6？M KOH), the optimal ZnO/CoOx@CNF sample produces an areal capacitance of 274 mF·cm？2 and a capacitance retention of 92？% after galvanostatic charge？discharge 40,000 cycles. Furthermore, the flexible supercapacitor cell exhibits a capacitance retention of 70？% after 1000 bending cycles, indicating the electrochemical stability and mechanical resilience of the ZnO/CoOx@CNF supercapacitor.